The Study of Fishing Port Networks to Support Buffer Areas in IKN - Putri, Destyariani Liana; Wirawan, Muhammad Khaisar; Huda, Abiyani Chairul; Aldovani, Ardian Audi; Natasya, Della (Universitas Jember, 2024)
East Kalimantan Province is a region in Indonesia where the mining and quarrying industry is still the main sector that influences the regional economy and Indonesia as a whole. However, local governments hast to make efforts to encourage other economic sectors to avoid a decline in economic growth which is influenced by fluctuations in world market prices. For example, the agricultural sector, including fisheries, is the most important potential commodity in East Kalimantan. The development of fishing ports in the coastal areas of East Kalimantan is very important as a center for local economic activities and also as a place to maintain the sustainability of fish resources. Apart from that, with the progress of the development of the New Capital City of Indonesia (IKN) in the Balikpapan and North Penajam Paser areas, it is important to review the function of the port as supporting water transportation connectivity in the IKN.